2001
DOI: 10.1159/000057237
|View full text |Cite
|
Sign up to set email alerts
|

Fernheilung und klinische Forschung

Abstract: Distant Healing and Clinical Research Distant healing is one of the most controversially discussed methods of complementary medicine. In the first section this paper outlines the history of spiritual healing and describes some possible definitions and different methods of spiritual healing. Based on a literature search in Medline, EMBASE, Current Contents, Allied and Complementary Medicine Database (AMED) as well as a manual tracking, current distant healing studies (excluding therapeutic touch studies) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Two reviews solely dealing with randomized controlled trials (RCTs) of healing found major methodological limitations in almost all the studies included and called for larger, methodologically sound RCTs [20,21]. Healing is generally practiced in two environments: (1) in direct or close physical contact between healee and healer, which is generally referred to as contact healing; and (2) at a distance without any physical contact, which is generally referred to as distant or remote healing [22]. Prayer is probably the best known and widely practiced form of distant healing in the western world.…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews solely dealing with randomized controlled trials (RCTs) of healing found major methodological limitations in almost all the studies included and called for larger, methodologically sound RCTs [20,21]. Healing is generally practiced in two environments: (1) in direct or close physical contact between healee and healer, which is generally referred to as contact healing; and (2) at a distance without any physical contact, which is generally referred to as distant or remote healing [22]. Prayer is probably the best known and widely practiced form of distant healing in the western world.…”
Section: Introductionmentioning
confidence: 99%
“…Ein Studienüberblick zum Thema Fernheilung wurde kürzlich in der FORSCHENDEN KOMPLEMENTÄRMEDIZIN publiziert [1]. Als weiteren Schritt zur Erhebung von Ausgangsdaten und zum Sammeln von Erfahrungen für eine im Anschluss geplante randomisierte Doppelblindstudie führten die Abteilung für Naturheilkunde an der Universitätsklinik Zürich und das Institut für Grenzgebiete der Psychologie und Psychohygiene Freiburg i.Br.…”
Section: Introductionunclassified